Problematika Autentifikasi Hadis Periode Sahabat: Antara Keadilan dan Intrik Politik - Anam, Wahidul; Ilaina, Rudhad (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This paper attempts to uncover the problematic authentication of hadith traditions of the Companion period regarding the concept of